JUDICIAL REVIEW OF LEGAL PROTECTION AGAINST VICTIMS IN THE PERSPECTIVE OF LAW NO. 13 OF 2006 CONCERNING PROTECTION OF WITNESSES AND VICTIMS - Setiono, Edi; Njoto, Harsono (Dinamika Hukum & Masyarakat, 2022)
Abstract The criminal justice system in Indonesia based on the Criminal Code (KUHAP) is too focused on the perpetrator and pays less attention to the victim. This can be seen in the lack of regulations contained in the Criminal Procedure Code that discusses the existence of crime victims. Thus, the position of a crime victim here is only as a witness in a criminal case which is solely to prove the suspect / defendant's guilt. The importance of a crime victim getting attention is based on the idea that the victim is the party who is aggrieved in the event of a crime, so that he should receive attention and service in order to provide protection for the interests of the victim, the crime victim is basically the party who suffers the most in an act. criminal. This study uses a descriptive method which aims to describe, summarize various conditions, various features or a description of certain conditions or variables. Thus it can be interpreted that the depiction or study of the data in the analysis is temporary, meaning that it can change according to developing circumstances and times. Every perpetrator of a criminal act must be held accountable for his actions where the rule of law is made to be obeyed, therefore if someone violates it must be subject to sanctions. In Indonesia, every sentence is imposed solely because someone has committed a crime. Keywords: legal protection, victim, crime